Derivation of 30 human embryonic stem cell lines—improving the quality - Ström, Susanne (Springer-Verlag, 2010)
We have derived 30 human embryonic stem cell lines from supernumerary blastocysts in our laboratory. During the derivation process, we have studied new and safe method to establish good quality lines. All our human embryonic stem cell lines have been derived using human foreskin fibroblasts as feeder cells. The 26 more recent lines were derived in a medium containing serum replacement instead of fetal calf serum. Mechanical isolation of the inner cell mass using flexible metal needles was used in deriving the 10 latest lines. The lines are karyotypically normal, but culture adaptation in two lines has been observed. Our human embryonic stem cell lines are banked, and they are available for researchers.